A Supply Chain Profile of a School-based Feeding Program using the Centralized Kitchen Model - Eden Delight Miro; J. Lemuel Martin; Leslie Lopez; Joselito Sescon; Carmela Oracion; Jhoel Loanzon (International Journal of Technology, 2018)
There has recently been renewed interest and a growing demand for school feeding programs. In the Philippines, the government, through the Department of Education (DepEd), Department of Social Welfare and Development (DSWD), and non-government organizations such as the Ateneo Center for Educational Development (ACED), has initiated such programs to address the prevalence of malnutrition among Filipino school-age children. In 2011, ACED introduced the ACED Blueplate Centralized Kitchen (ABCK) model for large-scale school feeding. This study aims to provide a supply chain profile of the first and largest city-wide implementation of the ABCK model in the Philippines to date, which is fully funded by a local government unit, DepEd, and DSWD. The research considers the crucial internal and external factors that influence the attainment of the program objectives, affect its performance, and promote its overall sustainability using the school feeding supply chain framework.